Nerves of the Hand beyond the Carpal Tunnel - Tagliafico, Alberto; Cadoni, Angela; Fisci, Erica; Gennaro, Sergio; Molfetta, Luigi; Perez, Maribel Miguel; Klauser, Andrea S.; Martinoli, Carlo (Seminars in Musculoskeletal Radiology, 2012)
Imaging studies including ultrasound (US) and magnetic resonance imaging may be required to evaluate the median nerve in patients with suspected carpal tunnel syndrome. However, the radial and ulnar nerves contribute to sensory and motor innervations to the hand as well. Compressive, traumatic, and iatrogenic events may damage the small terminal branches of these nerves. In the hand, US is able to identify injuries of the median, ulnar, radial nerve, and terminal branches. This article presents the role of imaging to evaluate the nerves of the hand with an emphasis on US. Due to its high-resolution capabilities, US is useful to determine the location, extent, and type of nerve lesion. Moreover, US is useful for a postsurgical assessment. The anterior interosseous nerve, Guyon's tunnel syndrome, and Wartenberg's syndrome are also described.
Keywords: ultrasound; anterior interosseous nerve; Guyon's tunnel; Wartenberg's syndrome; neuropathy